Handbook Seattle Art Museum. Selected Works from the Permanent Collections - Anonymus, A. (1951)
p. 12: fig. of a donor, Sumerian, probably from Khafaje; ca. 3000 B. C. - Boundary stone (kudurru), Kassite dyn. of Babylon; ca. 1300 B. C. — p. 14: Lions (stone relief). Persian, from the Hall of the Hundred Columns. Persepolis, reign of Artaxerxes I. — Tribut bearer carrying wine skin, from the Great Staircase of Persepolis, reign of Darius.